O neoliberalismo e a produção do espaço na metrópole: subjetividades, insurgências e redes na economia política da urbanização contemporânea - Felipe Nunes Coelho Magalhaes (2015)
Starting with the economic transformations which resulted from the productive restructuring initiated in the 1980s, this dissertation examines the intersections between neoliberalism and the production of space in the metropolis, defending the idea that the contemporary Brazilian city has its functioning and the structuring of its spaces directly linked to a set of forces and dynamics largely connected to neoliberalism. The argument departs from a discussion of the space of the state in neoliberalism, passing through a historical analysis of the formation of the Brazilian city related to macroeconomic transformations throughout the twentieth century, and reaching an assessment of the political economy of the contemporary metropolitan processes regarding their relation to a neoliberal mode of capitalist regulation. Further on, we analyze the symbolic dimension of the production of urban space and its relations to neoliberal "governmentality" (from Michel Foucaults perspective on the state-society relationships taken shape through these transformations). Heterotopias and spaces of resistance appear in this context as attempts to escape and resist from forms of discipline and control, which gain density through citizenship practices as a form of otherness. The encounter between networks formed in digital space and those in metropolitan space, as well as its political implications, are presented as a basis from which to better approach contemporary political movements in this urban context. The 2011 political mobilizations appear as a second bridge to finally analyse the June 2013 protests in Brazil, from a participant observation standpoint and seen as major political assemblages that result partially from this meeting between the internet and the city, largely constituted against the effects of neoliberalism and its constituent processes in everyday life and in the metropolis (also in their intersections). The conclusions propose a normative appreciation of the contemporary potentials of response to this broad framework, through diverse forms of action situated in the meeting grounds between the right to the city and the construction of openings connected to the common and radical democracy as complementary platforms, as already sought by some current social movements in practice.